2012
DOI: 10.1111/jpy.12020
|View full text |Cite
|
Sign up to set email alerts
|

Algal taxonomy: a road to nowhere?

Abstract: The widespread view of taxonomy as an essentially retrogressive and outmoded science unable to cope with the current biodiversity crisis stimulated us to analyze the current status of cataloguing global algal diversity. Contrary to this largely pessimistic belief, species description rates of algae through time and trends in the number of active taxonomists, as revealed by the web resource AlgaeBase, show a much more positive picture. More species than ever before are being described by a large community of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 78 publications
1
104
0
3
Order By: Relevance
“…On the other hand, in the case of algae and cyanobacteria, Brazil continues to face obstacles for the advancement in the knowledge of phycological diversity, be it because of global issues, such as the shortage of taxonomists specializing in this area (Guiry 2012;De Clerck et al 2013) or, in the regional scale, such as the lack of laboratory facilities and nonavailability of biological collections where the diversity is higher (Grieneisen et al 2014). Strategic policies have already been launched by the Brazilian government in order to accelerate the study of the country's biodiversity, however, these need to be strengthened and widened to ensure its mapping is more homogeneous and complete.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the case of algae and cyanobacteria, Brazil continues to face obstacles for the advancement in the knowledge of phycological diversity, be it because of global issues, such as the shortage of taxonomists specializing in this area (Guiry 2012;De Clerck et al 2013) or, in the regional scale, such as the lack of laboratory facilities and nonavailability of biological collections where the diversity is higher (Grieneisen et al 2014). Strategic policies have already been launched by the Brazilian government in order to accelerate the study of the country's biodiversity, however, these need to be strengthened and widened to ensure its mapping is more homogeneous and complete.…”
Section: Discussionmentioning
confidence: 99%
“…Previous queries into the ecology of snow algae have been limited mainly to community composition (Yoshimura et al 1997;Takeuchi 2013). The increasing use of DNA meta-bar-coding tools has elucidated the hidden diversity of algae and presents an opportunity to integrate these new discoveries with traditional taxonomy (De Clerck et al 2013). Snow algae have been described as simple communities that consist of few species (Takeuchi 2001) and are generally considered to occur in closed ecosystems (Hoham and Duval 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the advent of molecular systematics has demonstrated that the vegetative and reproductive characteristics traditionally used for species delimitation are not always consistent with the results of molecular phylogenetic approaches because of both convergence leading to cryptic diversity, and phenotypic plasticity causing variation in morphological characters (e.g. Saunders, 2005;Le Gall & Saunders, 2010;De Clerck et al, 2013). Reliable identification of seaweeds, based solely on morphological characters, is therefore a challenging task.…”
Section: Introductionmentioning
confidence: 99%